Production and characterization of shape memory polymeric nanocomposite materials - Canbay, C. Aksu; Unlu, N. (Elsevier, 2021)
Polymers are macromolecular materials that simple molecules (monomers) come together with chemical bonds and form them. The industrial use area of polymers is increasing due to many advantages of them such as mechanical properties, easy formability, lightweight, and low cost. Properties of smart (capable of reacting to an external effect) polymers; because of external effects such as magnetic field, electric field, temperature, and pH, they can change their shape and various mechanical properties. Areas such as aviation, construction, electronics, and medical can be given as examples to the usage areas of such materials. In this study, poly (vinyl alcohol) (PVA) polymer was used as a matrix in nanocomposite materials. New types of shape memory nanocomposites materials were obtained by using reduced graphene oxide (rGO) and graphene oxide (GO) produced by the Hummers method as fillers. Differential scanning calorimeter (DSC) and thermogravimetric analysis (TGA) devices were used to examine the thermal characterization of materials. X-ray diffraction (XRD) method and Fourier transform infrared spectrometry (FT-IR) were used for structural characterization analysis. In addition, chemical characterization of the materials was investigated using energy diffusion X-ray analysis (EDX) and surface morphology using scanning electron microscopy (SEM). The shape memory performances of the produced nanocomposite materials were determined by the shape recycling tests. It is examined the effect of fillers on the shape memory performance, structural and thermal properties of nanocomposite materials. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Nanocomposites; Reduced graphene oxide; Graphene oxide; Poly (vinyl alcohol); Shape memory polymeric nanocomposites